The Road to Dog Rabies Control and Elimination—What Keeps Us from Moving Faster? - Fahrion, Anna S.; Taylor, Louise H.; Torres, Gregorio; Müller, Thomas; Dürr, Salome; Knopf, Lea; de Balogh, Katinka; Nel, Louis H.; Gordoncillo, Mary Joy; Abela-Ridder, Bernadette (Frontiers in Public Health, 2017)
Rabies, a vaccine preventable neglected tropical disease, still claims an estimated 35,000–60,000 human lives annually. The international community, with more than 100 endemic countries, has set a global target of 0 human deaths from dog-transmitted rabies by 2030. While it has been proven in several countries and regions that elimination of rabies as a public health problem is feasible and tools are available, rabies deaths globally have not yet been prevented effectively. While there has been extensive rabies research, specific areas of implementation for control and elimination have not been sufficiently addressed. This article highlights some of the commonest perceived barriers for countries to implementing rabies control and elimination programs and discusses possible solutions for sociopolitical, organizational, technical, and resource-linked requirements, following the pillars of the global framework for the elimination of dog-mediated human rabies adopted at the global rabies meeting in December 2015.